From Suicide, to Acceptance through Faith, and then, to Defiant Revolt: Existential Absurdism in Albert Camus' The Stranger - Henke, Daniel (My University, 2013)
This thesis examines the three stages of resolving the Absurd in existential Absurdism highlighted by Albert Camus in The Myth of Sisyphus in an attempt to find meaning in life. It argues that the narrator Meursault in Albert Camus' The Stranger ventures through these three stages: suicide, acceptance through faith, and defiant revolt. In order to better understand the process and the motive behind Merusault's actions and human conditions, and to gain a deeper understanding of Absurdism, Freudian analysis is used to demonstrate Meursault's life in relation to the Absurd.
Thesis (M.A.--English Literature)
Keywords: Camus, Albert, 1913-1960. Etranger; Suicide in literature; Faith in literature; Absurd (Philosophy) in literature; Existentialism in literature